Comparative study of edge-functionalized graphene nanoplatelets as metal-free counter electrodes for highly efficient dye-sensitized solar cells. (September 2018) - Kim, Chang Ki; Kim, Hong Mo; Aftabuzzaman, M.; Jeon, In-Yup; Kang, Sung Ho; Eom, Yu Kyung; Baek, Jong Beom; Kim, Hwan Kyu
Abstract: Edge-functionalized graphene nanoplatelets (GnPs) were synthesized by a simple ball-milling process of graphite in the presence of halogen (F, I), metalloids (Se, Te and Sb) and subsequently applied to dye-sensitized solar cells (DSSCs) as counter electrodes (CEs). In our previous works, a series of edge-functionalized GnPs were thoroughly studied and successfully utilized as CEs in DSSCs, with the aim of finding possible alternatives to the noble and expensive Pt metal as CE. However, in each study, the GnP-CEs were not only fabricated with different dyes and electrolytes but were also evaluated on different occasions, and thus, it was difficult to identify which type of edge-functionalized GnPs was the best. Herein, DSSCs with different edge-functionalized GnP-CEs were fabricated under the same environmental conditions, photovoltaic performances were then evaluated employing both I − /I3 − and Co(bpy)3 2+/3+ (bpy = 2, 2′-bipyridine) redox couples with three different sensitizers to assess the electrocatalytic activity of the different GnP-CEs. Photovoltaic performances of edge-halogenated GnP-CEs with N719 dye employing the I − /I3 − redox couple were lower than those of the metalloid-doped GnP-CEs and were even inferior to Pt-CE, which was consistent with the R ct values. Conversely, among the metalloid-doped GnP-CEs, SbGnP-CE exhibited a higher R ct value and lower power conversion efficiency (PCE) value of 8.70% and 6.60% with N719 and SGT-130 dyes, respectively. However, when the devices were fabricated with the Co(bpy)3 2+/3+ redox couple, the opposite occurred and SbGnPs displayed the highest PCE of 10.42% with SGT-130 dye and 12.08% with SGT-021 dye. Furthermore, SeGnP-CE and TeGnP-CE showed superior compared to the Pt-CE with both I − /I3 − and Co(bpy)3 2+/3+ electrolyte solutions. Graphical abstract: Highlights: Edge-functionalized (F, I, Se, Te and Sb) graphene nanoplatelets (GnPs) were synthesized by a simple ball-milling process for DSSC CEs. PCE of edge-halogenated GnP-CEs employing the I − /I3 − redox couple was inferior to Pt-CE. Except SbGnP-CE, SeGnP-CE and TeGnP-CE shows superior PCE compared to Pt-CE employing the I − /I3 − redox couple. All metalloid-doped GnP-CEs show superior PCE compared to Pt-CE employing the Co(bpy) 32+/3+ redox couple.